2019
DOI: 10.3390/land8070103
|View full text |Cite
|
Sign up to set email alerts
|

Climate, Land Use and Land Cover Changes in the Bandama Basin (Côte D’Ivoire, West Africa) and Incidences on Hydropower Production of the Kossou Dam

Abstract: Climate and land use/cover changes are potential drivers of change in hydrology and water use. Incidences of these factors on Bandama hydrological basin and Kossou hydropower generation (1981–2016) in West Africa are assessed in this present work. Using Landsat products of United Stated Geological Survey, results show that water bodies areas and land use have increased by 1.89%/year and 11.56%/year respectively, whereas herbaceous savanna, savanna, forest and evergreen forest coverage have been reduced by 1.39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This could be attributed to climate change impacts and land use and land cover changes in the Bandama basin. In general, climate change and land use and land cover change play significant roles [26,27,29,53,54] to water availability. However, studies that distinguish the impact of climate change and land use and land cover changes or the combined effect of the two are limited.…”
Section: Resultsmentioning
confidence: 99%
“…This could be attributed to climate change impacts and land use and land cover changes in the Bandama basin. In general, climate change and land use and land cover change play significant roles [26,27,29,53,54] to water availability. However, studies that distinguish the impact of climate change and land use and land cover changes or the combined effect of the two are limited.…”
Section: Resultsmentioning
confidence: 99%
“…Any changes in land cover in the basin may result in changes in precipitation and discharge, which may affect the efficiency of the hydropower plant. For instance, Obahoundje et al (2018) showed how LULCC may influence the hydrology of three transboundary basins in WA, and Kouame et al (2019) illustrated how LULCC impacted the Kossou hydropower generation.…”
Section: Nexus Between Climate Land and Hydropower In Wamentioning
confidence: 99%
“… 3.An increase in ET by up to 0.84 %, 59.8 %, and 55.5 % under LULC, climate, and combined climate and LULC change 4.The magnitude of the shift in emissions under RCP8.5 is greater than that under RCP2.6 and RCP4.5. [ 77 ] Climate, Land Use and Land Cover Changes in the Bandama Basin (Côte D'Ivoire, West Africa) and Incidences on Hydropower Production of the Kossou Dam LULC Data Hydroclimatic and Energy Production Data Kriging method, Mann–Kendall test N/A 1.The outcome reveal that water bodies areas and LU have increased by 1.89 %/year and 11.56 %/year respectively 2.Streamflow presents greater change in magnitude compared to rainfall 3.Streamflow varies greatly than the rainfall does annually except during driest months possibly due to LULC change. 4.Kossou hydropower generation is significantly decreasing (p-value 0.007) at both monthly and annual scales possibly due to water abstraction at upstream [ 78 ] Land Use and Land Cover Changes under Climate Uncertainty: Modelling the Impacts on Hydropower Production in Western Africa Land Use and Land Cover Change data Rainfall and Stream Flow data WEAP Model No data 1.Historical rainfall analysis and stream flow changes shows variability in the annual coefficient of rainfall and stream flow as 8.6 % and 60.85 % respectively.…”
Section: Introductionmentioning
confidence: 99%